APPLICATION OF ADMINISTRATIVE SANCTIONS FOR PROBLEM HIGH PRIVATE EDUCATION IN EFFORTS TO IMPROVE EDUCATION QUALITY (STUDY SERVICE INSTITUTION FOR HIGHER EDUCATION IN REGION I OF NORTH SUMATRA) - ABD. AZIZ TAMBUNAN (LP2MTBM MAKARIOZ, 2020)
This study aims to determine the form of violations committed by managers of private tertiary institutions in the NorthSumatra Region I LLDikti area, to determine the law enforcement application of administrative sanctions for universities thatcommit violations within the North Sumatra Region I LLDikti environment and to determine the authority of the Region IHigher Education Service Institution North Sumatra in providing sanctions for universities that commit violations. This studyuses a normative legal research method with prescriptive analysis specifications using a statute approach, case approach toobtain secondary data as primary, secondary and tertiary legal material. The results of the study showed that there were stilluniversity institutions that committed violations with various forms of violations. The results of the study also explained thatlaw enforcement in applying administrative sanctions for problematic high-ranking companies used a preventive lawenforcement approach in the form of supervision without imposing sanctions. The results of the subsequent researchexplained that the authority of LLDikti for the application of sanctions already existed in Permendikbud 7 in 2020 but wasrarely used. It is expected that all elements of the LLDikti leadership and staff have the same perception of understanding thelaw enforcement mechanism in applying administrative sanctions as stipulated by the Republic of Indonesia Minister ofEducation Regulation No. 7 of 2020 for private universities that commit violations so that they can work in accordance withexisting rules open based on personal interpretation.